2009
DOI: 10.1007/s00253-009-2207-1
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective oxidation of indole- and quinolinecarboxylic acids by cytochrome P450 CYP199A2

Abstract: CYP199A2, a bacterial P450 monooxygenase from Rhodopseudomonas palustris, was previously reported to oxidize 2-naphthoic acid and 4-ethylbenzoic acid. In this study, we examined the substrate specificity and regioselectivity of CYP199A2 towards indole- and quinolinecarboxylic acids. The CYP199A2 gene was coexpressed with palustrisredoxin gene from R. palustris and putidaredoxin reductase gene from Pseudomonas putida to provide the redox partners of CYP199A2 in Escherichia coli. Following whole-cell assays, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…We explored the catalytic potential of CYP199A2 for the oxidation of coumaric and cinnamic acids. Whole-cell assays were performed using E. coli cells that coexpressed CYP199A2 with putidaredoxin reductase from P. putida and palustrisredoxin from R. palustris (12). HPLC analysis of the reaction of CYP199A2 with p-coumaric acid showed a major peak (retention time, 4.2 min) in addition to the substrate peak (5.7 min) (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We explored the catalytic potential of CYP199A2 for the oxidation of coumaric and cinnamic acids. Whole-cell assays were performed using E. coli cells that coexpressed CYP199A2 with putidaredoxin reductase from P. putida and palustrisredoxin from R. palustris (12). HPLC analysis of the reaction of CYP199A2 with p-coumaric acid showed a major peak (retention time, 4.2 min) in addition to the substrate peak (5.7 min) (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The wild-type or mutant CYP199A2 gene was coexpressed with the putidaredoxin reductase gene (pdR) from Pseudomonas putida (30) and the palustrisredoxin gene (pux) from R. palustris (2) to provide the redox partners of CYP199A2 in Escherichia coli. pET21a, carrying the wild-type or mutant CYP199A2 gene, and pMW218, carrying the pdR and pux genes, which was previously constructed (12), were simultaneously introduced into E. coli BL21(DE3) cells (Novagen). These recombinant E. coli cells were cultivated in LuriaBertani medium (1% Bacto tryptone, 0.5% Bacto yeast extract, 1% NaCl [pH 7.0]) supplemented with ampicillin (100 g/ml) and kanamycin (100 g/ml) at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The closely related CYP199A2 enzyme, from the CGA009 strain of R. palustris, has been reported to be a biocatalyst for the oxyfunctionalisation of 4-methoxybenzoic acid and various other aromatic carboxylic acids including 2-naphthoic, indole-6-carboxylic and cinnamic acids. [7,[17][18][19][20] Recently, the wild-type enzyme and mutant forms of CYP199A2…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…[1,17,19,21,32] In order to investigate the whole-cell turnover of these substrates, we utilised a system developed in our laboratory which produced CYP199A4, HaPux and HaPuR in E. coli. [1] Using low cell density cultures (3 g cell wet weight.L 1 ), we have shown that 4-methoxybenzoic acid was rapidly converted to 4-hydroxybenzoic acid with 2 mM substrate being completely turned over in less than 4 hours and 4 mM in 24 hours (Fig.…”
Section: Whole-cell Oxidation Turnover Assaysmentioning
confidence: 99%